Naturally Occurring Biventricular Noncompaction in an Adult Domestic Cat. (3rd February 2017) - Kittleson, M.D.; Fox, P.R.; Basso, C.; Thiene, G.
Abstract : A definitively diagnosed case of left ventricular noncompaction (LVNC) has not been previously reported in a non‐human species. We describe a Maine Coon cross cat with echocardiographically and pathologically documented LVNC. The cat was from a research colony and was heterozygous for the cardiac myosin binding protein C mutation associated with hypertrophic cardiomyopathy (HCM) in Maine Coon cats (A31P). The cat had had echocardiographic examinations performed every 6 months until 6 years of age at which time the cat died of an unrelated cause. Echocardiographic findings consistent with LVNC (moth‐eaten appearance to the inner wall of the mid‐ to apical region of the left ventricle (LV) in cross section and trabeculations of the inner LV wall that communicated with the LV chamber) first were identified at 2 years of age. At necropsy, pathologic findings of LVNC were verified and included the presence of noncompacted myocardium that consisted of endothelial‐lined trabeculations and sinusoids that constituted more than half of the inner part of the LV wall. The right ventricular (RV) wall also was affected. Histopathology identified myofiber disarray, which is characteristic of HCM, although heart weight was normal and LV wall thickness was not increased.